Biosilica nanoparticulate scavengers for the therapy of hepatic ischemia–reperfusion injury in preclinical models - Bingxin Zhou; Xuchun Chen; Renyu Ding; Zhongyun Bi; Tongyi Zhao; Ruilin Zhou; Miao Xu; Jiawen Li; Xinrui Jiang; Heran Li (Nature Communications)
Abstract Hepatic ischemia–reperfusion injury (IRI), involving intracellular Ca2+ overload, oxidative stress, inflammatory network, and microcirculation disturbance, remains unsolved clinically. Here, we design a biosilica nanoparticulate scavenger PEI-arg@MON@BA for IRI therapy, via a biomimetic silica–constructing program, based on the cooperative-assembly of cell-free DNA (cfDNA) binding polyethylenimine (PEI), reactive oxygen species (ROS) scavenger tetrasulfur-bridged mesoporous organosilica nanoparticles (MON), intracellular Ca2+ chelator BAPTA-AM, and nitric oxide (NO) substrate L-arginine (arg). It targets scavenging cfDNA, ROS, and intracellular Ca2+, and supplying NO, via electrostatic interaction, redox reaction, complexing action, and biotransformation, respectively. Intravenous administered PEI-arg@MON@BA passively targets to the liver, significantly attenuates hepatic damage, decreases oxidative stress, reduces cfDNA-induced TLR9–MyD88–NF-ĸB signaling, and inhibits the inflammatory cascade in both IRI model and liver transplantation (LT) model in male rats. It also eliminates the danger signals in LT patient serums, and relieves the ischemic injury in human liver tissues, pathing important clinical translation prospects.